ORMDL3 and Asthma: Linking Sphingolipid Regulation to Altered T Cell Function - Luthers, Christopher R.; Dunn, Teresa M.; Snow, Andrew L. (Frontiers in Immunology, 2020)
Orosomucoid like 3 (ORMDL3) encodes an ER-resident transmembrane protein that regulates the activity of serine palmitoyltransferase (SPT), the first and rate-limiting enzyme for sphingolipid biosynthesis in cells. A decade ago, several genome wide association studies revealed single nucleotide polymorphisms associated with increased ORMDL3 protein expression and susceptibility to allergic asthma. Since that time, numerous studies have investigated how altered ORMDL3 expression might predispose to asthma and other autoimmune/inflammatory diseases. In this brief review, we focus on growing evidence suggesting that heightened ORMDL3 expression specifically in CD4+ T lymphocytes, the central orchestrators of adaptive immunity, constitutes a major underlying mechanism of asthma pathogenesis by skewing their differentiation and function. Furthermore, we explore how sphingolipid modulation in T cells might be responsible for these effects, and how further studies may interrogate this intriguing hypothesis.